A self-assembled monolayer material based on conjugated linking groups and a preparation method thereof, and a solar cell

By introducing self-assembled single-layer material based on conjugated connecting groups into trans perovskite solar cells, the problem of poor stability of hole transport layer materials is solved, and efficient and stable photoelectric conversion efficiency and device performance are achieved.

CN117659083BActive Publication Date: 2025-01-03SHENZHEN MOLE NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311417935.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-01-03
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The commonly used hole transport layer materials in existing trans perovskite solar cells have problems such as poor stability, messy orientation and low layout density, which limits the performance improvement of devices and commercial applications.

Method used

Self-assembled single-layer material based on conjugated linking groups is introduced, and prepared by Ulmann reaction and palladium-catalyzed carbon-phosphine bond coupling reaction to form a self-assembly layer with high intrinsic stability and excellent photoelectric properties.

Benefits of technology

The stability and hole extraction capability of the single-molecule self-assembly layer are significantly improved, interface contact and energy level matching are improved, and efficient and stable photoelectric conversion efficiency and device performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117659083B_ABST
    Figure CN117659083B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of optoelectronic devices, and in particular to a self-assembled monolayer material based on a conjugated linking group, a preparation method thereof, and a solar cell. The chemical structure general formula of the self-assembled monolayer material based on a conjugated linking group is: #imgabs0# wherein the electron donor is one of an electron-rich group and its derivatives; and L is a conjugated linking group. Introducing a conjugated linking group to replace a non-conjugated alkyl linking group in the self-assembled monolayer material can effectively achieve electron delocalization, enhance the intrinsic stability of the monomolecular self-assembled layer molecules, and the hole extraction and transmission capabilities; in addition, due to its rigid structure, the order and density of the molecular arrangement of the monomolecular self-assembled layer are significantly improved. Moreover, the self-assembled monolayer material can form a dense monomolecular self-assembled layer on the surface of a conductive substrate, improve interface contact, and passivate interface defects; it can form a dipole on the surface of a conductive substrate, improve the surface work function, and promote hole transmission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optoelectronic devices, and in particular to a self-assembled monolayer material based on a conjugated linking group, a preparation method thereof, and a solar cell. Background Art

[0002] Perovskite solar cells are a new type of photovoltaic device that uses semiconductor materials with a perovskite structure as a light absorption layer to achieve efficient photoelectric conversion. A trans-perovskite solar cell is a type of perovskite solar cell that uses a trans-structure, that is, a hole transport layer is inserted between the substrate electrode and the perovskite layer, and an electron transport layer is inserted between the perovskite layer and the transparent electrode. This structure can effectively improve the selective extraction and transport of carriers, thereby improving the efficiency and stability of the device. At present, trans-perovskite solar cells have achieved the world's highest efficiency of 25.7%, exceeding the efficiency of polycrystalline silicon solar cells; however, the hole transport layers commonly used in trans-perovskite solar cells, such as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), nickel oxide (NiO x ), PEDOT:PSS, still have defects such as low wettability, poor interface contact or difficulty in preparing large-area devices, which limit their further performance improvement and commercial application.

[0003] In order to solve these problems, an effective strategy is to introduce a self-assembled monolayer between the perovskite layer and the electrode to improve the interface quality and charge extraction; the self-assembled monolayer is an effective single-molecule array spontaneously formed by organic molecules on the solid surface, and the interface properties can be precisely controlled by adjusting the molecular structure and functional groups. Currently, widely used self-assembled molecular layer materials such as [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl] acid phosphine have a certain solubility in common polar solvents such as methanol, ethanol, isopropanol, and N,N'-dimethylformamide, and can form a single-molecule self-assembled layer by simple methods such as immersion or spin coating. However, the single-molecule self-assembled layer materials containing alkyl chain connecting groups have defects such as poor stability, disordered orientation, and low arrangement density. Although great progress has been made, problems such as improving the stability of inverse perovskite solar cell devices and further improving the photoelectric conversion efficiency still need to be solved. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a self-assembled monolayer material based on conjugated linking groups, a preparation method thereof, and a solar cell, aiming to solve the problems of poor stability, disordered orientation, low arrangement density, etc. of the existing monomolecular self-assembled layer materials containing alkyl chain linking groups.

[0005] The technical solution of the present invention is as follows:

[0006] A self-assembled monolayer material based on a conjugated linking group, wherein the chemical structure of the self-assembled monolayer material based on a conjugated linking group is:

[0007]

[0008] The electron donor is one of the electron-rich groups and their derivatives; and L is a conjugated connecting group.

[0009] A method for preparing a self-assembled monolayer material based on a conjugated linking group comprises the steps of:

[0010] An electron-rich compound containing an imine structure undergoes an Ullmann reaction with a conjugated compound containing two halogen groups to obtain a first intermediate;

[0011] The first intermediate is subjected to a palladium-catalyzed carbon-phosphine bond coupling reaction to obtain a second intermediate containing a phosphonate;

[0012] The alkoxy group in the second intermediate containing phosphonate is converted into a hydroxyl group by using trimethylsilyl bromide to obtain the self-assembled monolayer material based on the conjugated connecting group.

[0013] A solar cell, characterized in that the solar cell comprises a self-assembled monolayer or a hole transport layer, and the self-assembled monolayer or the hole transport layer comprises the self-assembled monolayer material based on conjugated linking groups.

[0014] Beneficial effects: The present invention provides a self-assembled monolayer material based on a conjugated linking group, a preparation method thereof, and a solar cell. The chemical structure of the self-assembled monolayer material based on a conjugated linking group is as follows: Wherein, the electron donor is one of the electron-rich groups and their derivatives; L is a conjugated linking group. Introducing a conjugated linking group to replace the non-conjugated alkyl linking group in the self-assembled monolayer material can effectively achieve electron delocalization, enhance the intrinsic stability of the monomolecular self-assembled layer molecules and the hole extraction and transmission capabilities; in addition, due to its rigid structure, the order and density of the molecular arrangement of the monomolecular self-assembled layer are significantly improved. And the self-assembled monolayer material based on the conjugated linking group can form a dense monomolecular self-assembled layer on the surface of the conductive substrate, improve the interface contact, and passivate the interface defects; it can form a dipole on the surface of the conductive substrate, improve the surface work function, and promote hole transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the MeCz-PhBr hydrogen nuclear magnetic resonance spectrum in Example 1;

[0016] Figure 2is the hydrogen nuclear magnetic resonance spectrum of MeCz-PhP in Example 1;

[0017] Figure 3 is the hydrogen nuclear magnetic resonance spectrum of Me-PhpPACz in Example 1;

[0018] Figure 4 Schematic diagram of the structure of an inverted planar heterojunction perovskite solar cell;

[0019] Figure 5 JV curve of perovskite solar cell based on transport layer Me-PhpPACz;

[0020] Figure 6 is the Cz-PhBr hydrogen nuclear magnetic resonance spectrum in Example 2;

[0021] Figure 7 is the hydrogen nuclear magnetic resonance spectrum of Cz-PhP in Example 2;

[0022] Figure 8 is the proton nuclear magnetic resonance spectrum of PhpPACz in Example 2;

[0023] Fig. 9 This is a JV curve diagram of a perovskite solar cell based on a transport layer PhpPACz in Example 2;

[0024] Fig.10 is the MeOCz-PhBr hydrogen nuclear magnetic resonance spectrum in Example 3;

[0025] Fig.11 is the proton nuclear magnetic resonance spectrum of MeOCz-PhP in Example 3;

[0026] Fig.12 is the hydrogen nuclear magnetic resonance spectrum of MeO-PhpPACz in Example 3;

[0027] Fig.13 JV curve of perovskite solar cell based on transport layer MeO-PhpPACz;

[0028] Fig.14 is the NapCz-PhBr hydrogen nuclear magnetic resonance spectrum in Example 4;

[0029] Fig.15 is the hydrogen nuclear magnetic resonance spectrum of NapCz-PhP in Example 4;

[0030] Fig.16 is the hydrogen nuclear magnetic resonance spectrum of Nap-PhpPACz in Example 4;

[0031] Fig.17 JV curve of perovskite solar cell based on transport layer Nap-PhpPACz;

[0032] Fig.18 is the MMT-PhBr hydrogen nuclear magnetic resonance spectrum in Example 5;

[0033] Fig.19 is the hydrogen nuclear magnetic resonance spectrum of MMT-PhP in Example 5;

[0034] Fig. 20 is the hydrogen nuclear magnetic resonance spectrum of MMT-PhpPACz in Example 5;

[0035] Fig.21 JV curve of perovskite solar cell based on transport layer MMT-PhpPACz;

[0036] Fig. 22 is the proton nuclear magnetic resonance spectrum of MONCz-PhBr in Example 6;

[0037] Fig.23 is the hydrogen nuclear magnetic resonance spectrum of MONCz-PhP in Example 6;

[0038] Fig.24 is the hydrogen nuclear magnetic resonance spectrum of MON-PhpPACz in Example 6;

[0039] Fig.25 JV curve of perovskite solar cell based on transport layer MON-PhpPACz;

[0040] Fig.26 The structure diagram of the perovskite device containing a single molecular layer in Comparative Example 1;

[0041] Fig. 27 It is the IV curve diagram of the perovskite solar cell of comparative example 1;

[0042] Fig.28 This is a stability test diagram of the perovskite solar cell device of comparative example 1. DETAILED DESCRIPTION

[0043] The present invention provides a self-assembled monolayer material based on a conjugated linking group and a preparation method thereof, and a solar cell. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0044] Self-assembled molecular layers can be used as intermediate connectors to achieve tight bonding between layers, regulate interface energy levels, inhibit interface defects, promote charge extraction and transport, etc. The self-assembled monolayer materials currently widely used usually have the following structures: 1. Head groups, such as electron donors such as carbazole and phenothiazine, can passivate interface defects, regulate energy levels, and achieve efficient charge extraction and transport; 2. Connecting groups, such as alkyl chains of different lengths, provide self-assembly flexibility for the material; 3. Anchoring groups, such as phosphonic acid, can form effective covalent bonds with commonly used transparent conductive substrates through chemical reactions, and have been proven to be the most tightly bound anchoring groups to specific metal oxides among similar groups.

[0045] However, existing single-molecule self-assembled layer materials containing alkyl chain connecting groups have defects such as poor stability, disordered orientation, and low arrangement density. Although great progress has been made, problems such as improving the stability of solar cell devices and further improving the photoelectric conversion efficiency still need to be solved.

[0046] Based on this, Figure 1 As shown, the present invention provides a self-assembled monolayer material based on a conjugated linking group, and the chemical structure formula of the self-assembled monolayer material based on a conjugated linking group is:

[0047]

[0048] The electron donor is one of the electron-rich groups and their derivatives; and L is a conjugated connecting group.

[0049] In this embodiment, a conjugated linking group is introduced into the self-assembled monolayer material to replace the non-conjugated alkyl linking group, and a series of self-assembled monolayer materials based on conjugated linking groups are constructed, aiming to enhance its intrinsic stability, improve self-assembly performance, and improve hole extraction and transmission capabilities. The comparison of cyclic voltammetry and nuclear magnetic resonance detection before and after illumination shows that compared with the monomolecular self-assembled layer material of the non-conjugated linking group, the self-assembled monolayer material based on the conjugated linking group has higher electrochemical and photostability, which is dissolved in an alcohol solvent, and a monomolecular self-assembled layer is formed on the surface of the conductive substrate by spin coating. It is confirmed by XPS surface scanning that it forms a tighter monomolecular self-assembled layer. At the same time, based on the dipole moment and molecular orientation of the material, the surface work function of the conductive substrate is significantly improved.

[0050] Specifically, the self-assembled monolayer material based on conjugated linking groups provided in this embodiment has the following beneficial effects: (1) the self-assembled monolayer material based on conjugated linking groups has obvious electron delocalization and high intrinsic stability; (2) the self-assembled monolayer material based on conjugated linking groups can form a denser self-assembled layer on a conductive substrate; (3) the surface work function of the conductive substrate can be effectively regulated; (4) the monomolecular self-assembled layer can have stronger hole extraction and transmission capabilities.

[0051] In some embodiments, the electron donor in the chemical structural formula is an electron-rich group such as carbazole, phenothiazine, phenoxazine, diphenylamine, and its derivatives; L in the chemical structural formula is a conjugated linking group such as benzene, biphenyl, anthracene, phenanthrene, pyrene, pyridine, pyrimidine, furan, thiophene, quinoline, etc. The self-assembled monolayer material based on the conjugated linking group forms a self-assembled monolayer on a transparent conductive substrate during the spin coating process through the anchoring effect of the phosphate group on the metal oxide, which can adjust the surface work function of the conductive glass and improve the interface energy level matching; at the same time, the conjugated linking group in this type of material can enhance the interaction between molecules within the layer to form a denser monomolecular self-assembled layer; and the conjugated linking group has strong conductivity and can promote charge transfer. In addition, since the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) are localized in the electron donor and the conjugated linking group L, respectively, this type of material has excellent light and electrical stability.

[0052] In some embodiments, the electron donor is selected from

[0053]

[0054]

[0055] One of;

[0056] Among them, R1-R 14 are independently selected from hydrogen, deuterium, -F, -Cl, -Br, -I, hydroxyl, cyano, nitro, amino, amidino, hydrazine, hydrazone, C1-C 60 Alkyl, C2-C 60 Alkenyl, C2-C 60 Alkynyl, C1-C 60 Alkoxy, C3-C 60 Cycloalkyl, C1-C 10 Heterocycloalkyl, C3-C 10 Cycloalkenyl, C1-C 10 Heterocycloalkenyl, C6-C 60 Aryl, C1-C 60One of a heteroaryl group, a monovalent non-aromatic condensed polycyclic group, a monovalent non-aromatic condensed heteropolycyclic group, a biphenyl group, and a terphenyl group.

[0057] In some embodiments, the L is selected from

[0058] One of them.

[0059] In addition, the present invention also provides a method for preparing a self-assembled monolayer material based on a conjugated linking group, comprising the steps of:

[0060] Step S10: subjecting an electron-rich compound containing an imine structure to an Ullmann reaction with a conjugated compound containing two halogen groups to obtain a first intermediate;

[0061] Step S20: subjecting the first intermediate to a palladium-catalyzed carbon-phosphine bond coupling reaction to obtain a second intermediate containing a phosphonate;

[0062] Step S30: using trimethylsilyl bromide to convert the alkoxy group in the second intermediate containing the phosphonate into a hydroxyl group, so as to obtain the self-assembled monolayer material based on the conjugated linking group.

[0063] In this embodiment, an electron donor containing an imine (-NH-) structure is first subjected to an Ullmann reaction with a conjugated linker X1-L-X2 containing two halogen groups -X1, -X2 (-I, -Br, -Cl, -F) to obtain a first intermediate; then, the first intermediate is subjected to a palladium-catalyzed carbon-phosphine bond coupling reaction to obtain a second intermediate containing a phosphonate; finally, the alkoxy group (-OR) in the phosphonate in the second intermediate is converted into a hydroxyl group (-OH) by trimethylsilyl bromide (TMSBr) to obtain a self-assembled monolayer material based on a conjugated linker group.

[0064] Specifically, the synthetic route of the preparation method of the self-assembled monolayer material based on the conjugated linking group is as follows:

[0065]

[0066] In some embodiments, the step of subjecting the electron donor containing an imine structure to an Ullmann reaction with a conjugated linker containing two halogen groups to obtain a first intermediate comprises: in an inert gas atmosphere, mixing the electron donor, the conjugated linker and a catalyst, a ligand, a base and a solvent to obtain a reaction system; heating the reaction system to a first reflux temperature and keeping it warm for a first predetermined time to obtain the first intermediate.

[0067] In some embodiments, the catalyst is at least one of copper powder, cuprous oxide, cuprous iodide, cuprous bromide, and cuprous chloride; the ligand is at least one of L-proline, 18-crown ether-6, 1,2-cyclohexanediamine, 1,10-phenanthroline, and oxalyl diamide ligands; the base is at least one of potassium carbonate, potassium hydroxide, potassium phosphate, and potassium tert-butoxide; and the solvent is an organic solvent.

[0068] For example, an electron donor (1 equivalent) and a conjugated linker (2 equivalents) are mixed in a reaction system with cuprous iodide (0.1 equivalent) as a catalyst, 1,2-cyclohexanediamine (0.2 equivalent) as a ligand, potassium phosphate (3 equivalents) as a base, and toluene as a solvent under an inert gas atmosphere, and heated to a first reflux temperature for a first predetermined time to obtain the first intermediate; the first reflux temperature is 105-115° C., and the first predetermined time is 12-48 hours. Preferably, the first reflux temperature is 110° C.

[0069] In some embodiments, the step of subjecting the first intermediate to a palladium-catalyzed carbon-phosphine bond coupling reaction to obtain a second intermediate containing a phosphonate comprises: mixing the first intermediate with diethyl phosphite in an inert gas atmosphere in a reaction system comprising palladium acetate as a catalyst, 1,1'-bis(diphenylphosphino)ferrocene as a ligand, triethylamine as a base, potassium acetate as an additive, and tetrahydrofuran as a solvent to obtain a mixed solution; heating the mixed solution to a second reflux temperature and keeping it warm for a second predetermined time to obtain the second intermediate containing a phosphonate.

[0070] For example, in the inert gas range, the first intermediate (1 equivalent) and diethyl phosphite (1 equivalent) are mixed in a reaction system with palladium acetate (0.025 equivalent) as a catalyst, 1,1'-bis(diphenylphosphino)ferrocene (0.05 equivalent) as a ligand, triethylamine (1.2 equivalents) as a base, potassium acetate (0.1 equivalents) as an additive, and tetrahydrofuran as a solvent, and heated to a second reflux temperature and maintained for a second predetermined time to obtain a second intermediate containing a phosphonate; the second reflux temperature is 64-68°C, and the second predetermined time is 12-24 hours; preferably, the second reflux temperature is 66°C.

[0071] In some embodiments, the step of converting the alkoxy group in the second intermediate containing the phosphonate into a hydroxyl group using trimethylsilyl bromide to obtain the self-assembled monolayer material based on the conjugated linking group comprises: mixing trimethylsilyl bromide with the second intermediate containing the phosphonate in anhydrous dichloromethane or 1,4-dioxane in an inert gas atmosphere to obtain a mixed solution; after the mixed solution is reacted at room temperature for a third predetermined time, the self-assembled monolayer material based on the conjugated linking group is obtained.

[0072] For example, trimethylsilyl bromide (4 equivalents) is mixed with the second intermediate containing the phosphonate in anhydrous dichloromethane or 1,4-dioxane in an inert gas atmosphere, and then reacted at room temperature for 12-24 hours, followed by quenching with methanol or water to convert the alkoxy groups contained in the phosphonate in the second intermediate into hydroxyl groups to obtain the self-assembled monolayer material based on the conjugated linking group.

[0073] In addition, the present invention also provides a solar cell, which comprises a self-assembled monolayer or a hole transport layer, wherein the self-assembled monolayer or the hole transport layer comprises the self-assembled monolayer material based on conjugated linking groups.

[0074] In this embodiment, the self-assembled monolayer material based on conjugated linking groups is used in solar cells. This type of material can effectively improve the quality of the monomolecular self-assembled layer, enhance stability and hole extraction ability, improve interface contact and energy level arrangement, and realize a solar cell with high efficiency and good stability.

[0075] In some embodiments, the solar cell includes one or more of a perovskite solar cell or an organic solar cell; the perovskite solar cell is a lead-based ABX3 compound. The electron donor in the self-assembled monolayer material based on the conjugated linking group can directly contact the lower interface of the perovskite, and the passivation group can be introduced by reasonable molecular modification to passivate the interface defects, which is conducive to the formation of a high-quality perovskite film.

[0076] Specifically, the self-assembled monolayer material based on the conjugated linking group is used on the surface of conductive glass, perovskite, tin oxide, titanium oxide, aluminum oxide or nickel oxide, and a solar cell based on the self-assembled monolayer material is manufactured.

[0077] In some embodiments, the conductive glass includes but is not limited to one or more metal oxides such as FTO, ITO, and AZO.

[0078] In some embodiments, the nickel oxide is nickel monoxide or nickel trioxide.

[0079] In a preferred embodiment, the perovskite solar cell is an inverted perovskite solar cell; the monomolecular self-assembled layer material containing a conjugated linking group is applied to the inverted perovskite solar cell device, which improves the hole extraction ability, improves the stability of the reactive perovskite solar cell, and realizes a high-efficiency device with a high open circuit voltage and a high fill factor. At the same time, this type of material has the advantages of a short preparation process and low consumption, which is conducive to further realizing the large-scale, low-cost preparation and commercialization of inverted perovskite solar cell devices. The monomolecular self-assembled layer material based on the conjugated group has high intrinsic stability and hole extraction ability, and the inverted perovskite solar cell prepared based on this type of material has the advantages of good repeatability, high photoelectric conversion efficiency, and good device performance stability.

[0080] Specifically, the self-assembled monolayer material based on the conjugated linking group can effectively adjust the surface work function of the conductive glass, improve the interface contact, promote charge conduction, and realize efficient and stable inverted perovskite solar cells. Based on the strong anchoring effect of the phosphate group on common metal oxides, this type of material can also be widely used in the fields of optoelectronic devices such as perovskite light-emitting diodes, organic solar cells, organic light-emitting diodes, and field-effect transistors.

[0081] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0082] Example 1

[0083] The synthetic compound Me-PhpPACz is synthesized by the following synthesis route:

[0084]

[0085] 1. Synthesis of MeCz-PhBr

[0086] 3,6-Dimethylcarbazole (1.95 g, 10 mmol), 1-bromo-4-iodobenzene (5.66 g, 20 mmol), cuprous iodide (0.190 g, 1 mmol), 1,2-cyclohexanediamine (0.228 g, 2 mmol) and potassium phosphate (6.37 g, 30 mmol) were added to a dried 250 mL double-necked flask. Under an argon environment, 50 mL of toluene was added and heated to reflux for 12 hours. After the reaction mixture was cooled to room temperature, the system was extracted with dichloromethane and saturated brine, and the organic phases were combined and dried over anhydrous sodium sulfate. The dried solution was distilled to remove the solvent to obtain a crude product, which was further purified by column chromatography using silica gel as the stationary phase and dichloromethane and petroleum ether as eluents to obtain 3.32 g of a white solid product (95%), which is MeCz-PhBr. The hydrogen nuclear magnetic resonance spectrum of MeCz-PhBr is shown in Figure 1 As shown, the H NMR spectrum data is: 1 H NMR (400 MHz, CDCl3) δ7.93-7.88 (m, 2H), 7.74-7.68 (m, 2H), 7.47-7.41 (m, 2H), 7.28 (d, J = 8.3 Hz, 2H), 7.22 (dd, J = 8.5, 1.7 Hz, 2H), 2.55 (s, 6H), indicating that MeCz-PhBr was successfully synthesized.

[0087] 2. Synthesis of MeCz-PhP

[0088] Palladium acetate (16.8 mg, 0.075 mmol), 1,1'-bis(diphenylphosphino)ferrocene (83.2 mg, 0.15 mmol), potassium acetate (29.4 mg, 0.3 mmol) and MeCz-PhBr (1.05 g, 3 mmol) were added to a dried 100 mL two-necked flask. Then triethylamine (364 mg, 3.6 mmol) and 30 mL of tetrahydrofuran treated with argon bubbling were added, and the reaction mixture was stirred at a boiling state for 15 minutes. Diethyl phosphite (414 mg, 3 mmol) was then added and continued to stir at a boiling state for 12 hours. After cooling to room temperature, the reaction mixture was filtered through diatomaceous earth and rinsed with tetrahydrofuran. The filtrate was used to remove the solvent using a rotary evaporator, and the crude product was purified by silica gel column chromatography to obtain a white solid product (1.15 g, 94%), which is MeCz-PhP. The hydrogen nuclear magnetic resonance spectrum of MeCz-PhP is as follows Figure 2 As shown, the H NMR spectrum data is: 1H NMR (400 MHz, CDCl3) δ8.07-7.98 (m, 2H), 7.89 (d, J = 1.8 Hz, 2H), 7.74-7.65 (m, 2H), 7.37 (d, J = 8.4 Hz, 2H), 7.22 (dd, J = 8.5, 1.8 Hz, 2H), 4.35-4.09 (m, 4H), 2.54 (s, 6H), 1.40 (t, J = 7.1 Hz, 6H), indicating that MeCz-PhP was successfully synthesized.

[0089] 3. Synthesis of Me-PhpPACz

[0090] Under argon environment, 20mL of dichloromethane was added to a 50mL double-necked flask containing MeCz-PhP (0.407g, 1mmol). Under stirring, trimethylsilyl bromide (0.612g, 4mmol) was added dropwise, and the reaction mixture was stirred for 12 hours. The reaction mixture was transferred to a 100mL round-bottom flask, the solvent was removed using a rotary evaporator, and 20mL of methanol was added and stirred for 4 hours. After the reaction was completed, the solvent was removed again using a rotary evaporator to obtain a crude product, and the product was recrystallized using a methanol / dichloromethane / ether system to obtain a white solid product (0.350g, 99.5%). The hydrogen nuclear magnetic resonance spectrum of Me-PhpPACz is shown in Figure 3 As shown, the H NMR spectrum data is: 1 H NMR (400 MHz, DMSO-d6) δ8.05-7.90 (m, 4H), 7.70 (dd, J=8.4, 2.9 Hz, 2H), 7.35 (d, J=8.4 Hz, 2H), 7.23 (dd, J=8.5, 1.3 Hz, 2H), 2.48 (s, 6H), indicating that Me-PhpPACz was successfully synthesized.

[0091] 4. Use the prepared Me-PhpPACz in solar cells

[0092] The Me-PhpPACz prepared in step 3 can be used in perovskite solar cells and organic solar cells. Specifically, taking the inverted planar heterojunction perovskite solar cell as an example, the structural schematic diagram of the inverted planar heterojunction perovskite solar cell involved in this embodiment is as shown in Figure 4 As shown, from bottom to top, it includes: (1) transparent conductive substrate ITO; (2) Me-PhpPACz monomolecular self-assembled layer (SAM) or hole transport layer; (3) perovskite light absorption layer; (4) electron transport layer (C60); (5) copper or silver electrode. The preparation of inverted planar heterojunction perovskite solar cells specifically includes the following steps:

[0093] 1) Cleaning the transparent conductive substrate ITO

[0094] The etched transparent conductive substrate ITO was ultrasonically treated in a cleaning agent, deionized water, anhydrous ethanol, acetone, and isopropanol for 15 minutes in sequence, taken out and blown dry with clean air, placed in an oven, dried at 120°C for 8 hours, and treated with UV / ozone for 30 minutes.

[0095] 2) Preparation of single molecule self-assembled layer (SAM)

[0096] A Me-PhpPACz solution was prepared; the solution was spin-coated on a transparent conductive substrate ITO at a rotation speed of 4000 rpm for 40 seconds; and the obtained film was annealed in nitrogen at 100° C. for 10 minutes.

[0097] 3) Preparation of perovskite light absorbing layer

[0098] Any ABX3 is a perovskite structure, where A is any organic cation, such as formamidine (FA), methylamine (MA), etc.; B is any metal cation, such as lead, tin, etc.; X is any halogen anion, such as chlorine, bromine, iodine, etc.; ABX3 is prepared by dissolving it in a solvent such as DMF, DMSO, NMP, etc. Spin coating on ITO in two steps, specifically 1000rpm10s and 6000rpm20s (1000 rpm 10 seconds and 6000 rpm 20 seconds). When 5 seconds are left, chlorobenzene is dropped in the middle of the substrate, and the film is annealed at 100°C for 0.5 hours.

[0099] 4) Preparation of electron transport layer

[0100] In 1×10 -6 Pa vacuum, C60 was deposited on the perovskite surface.

[0101] 5) Preparation of copper or silver electrodes

[0102] In 1×10 -6 Pa vacuum degree, Copper or silver electrodes were prepared by rate evaporation deposition, and the electrode thickness was controlled to be ~100 nm.

[0103] 6) Testing

[0104] The device structure of the planar heterojunction perovskite solar cell prepared by the above method is as follows Figure 4 As shown, the effective area is 0.1cm 2 . Test conditions: spectral distribution AM1.5G, light intensity 100mW / cm 2 , AAA solar simulator (Beijing Zhuoli Hanguang Company), and the JV curve was measured using a Keithly 2400 digital source meter.

[0105] Test results see Figure 5The best photoelectric conversion efficiency parameters were: open circuit voltage 1.19V, short circuit current density 25.4mA / cm 2 , fill factor 87.1%, conversion efficiency 26.2%. After the device was stored in the atmosphere for 3000 hours, it still maintained more than 99% of the initial efficiency.

[0106] Example 2

[0107] The synthetic compound PhpPACz, the synthetic route of which is as follows:

[0108]

[0109] 1. Synthesis of Cz-PhBr

[0110] The raw material 3,6-dimethylcarbazole used to synthesize MeCz-PhBr in Example 1 was replaced with an equal amount of carbazole, and Cz-PhBr (2.67 g, 82.9%) was obtained according to the synthesis method of MeCz-PhBr. The H NMR spectrum of Cz-PhBr is shown in Figure 6 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 8.16(d,J=7.7Hz,2H),7.78-7.69(m,2H),7.49-7.41(m,4H),7.39(dt,J=8.1,1.2Hz,2H),7.32(ddd,J=8.0,6.8,1.4Hz,2H).

[0111] 2. Synthesis of Cz-PhP

[0112] The raw material MeCz-PhBr used to synthesize MeCz-PhP in Example 1 was replaced with an equal amount of Cz-PhBr, and Cz-PhP (0.962 g, 84.5%) was obtained according to the synthesis method of MeCz-PhP. The hydrogen nuclear magnetic resonance spectrum of Cz-PhP is shown in Figure 7 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 8.15(dt,J=7.8,1.0Hz,2H),8.10-8.01(m,2H),7.76-7.68(m,2H),7.48(dt,J=8.2,1.0Hz,2H),7.43(d dd,J=8.2,6.9,1.2Hz,2H),7.32(ddd,J=7.9,6.9,1.2Hz,2H),4.33-4.13(m,4H),1.41(t,J=7.1Hz,6H).

[0113] 3. Synthesis of PhpPACz

[0114] The raw material MeCz-PhP used to synthesize Me-PhpPACz in Example 1 was replaced with an equal amount of Cz-PhP, and PhpPACz (0.310 g, 95.8%) was obtained according to the synthesis method of Me-PhpPACz. The nuclear magnetic resonance hydrogen spectrum of PhpPACz is shown in Figure 8 As shown, the H NMR spectrum data is: 1 H NMR(400MHz,DMSO-d6)δ / ppm 8.26(d,J=7.7Hz,2H),7.97(dd,J=12.6,8.3Hz,2H),7.75(dd,J=8.3,2.9Hz,2H),7.48-7.41(m,4H),7.31(ddd,J=7.9,5.1,3.0Hz,2H).

[0115] 4. Preparation of solar cell devices

[0116] The solar cell involved in this embodiment involves a perovskite solar cell and an organic solar cell, and specifically takes an inverted planar heterojunction perovskite solar cell as an example. Figure 4 1 is a schematic diagram of the structure of the inverted planar heterojunction perovskite solar cell involved in this embodiment, which includes, from bottom to top: (1) a transparent conductive substrate ITO; (2) a single molecule self-assembled layer (SAM) of PhpPACz or a hole transport layer; (3) a perovskite light absorbing layer; (4) an electron transport layer (C60); and (5) a copper or silver electrode.

[0117] 1) Cleaning the transparent conductive substrate ITO: the same as in Example 1;

[0118] 2) Preparation of single molecule self-assembled layer (SAM)

[0119] A solution of PhpPACz was prepared; the solution was spin-coated on a transparent conductive substrate ITO at a speed of 4000 rpm for 40 seconds; the obtained film was annealed in nitrogen at 100° C. for 10 minutes;

[0120] 3) Preparation of perovskite light absorbing layer: the same as in Example 1;

[0121] 4) Preparation of electron transport layer: the same as in Example 1;

[0122] 5) Preparation of copper or silver electrodes: the same as in Example 1;

[0123] 6) Testing

[0124] The device structure of the planar heterojunction perovskite solar cell prepared by the above method is as follows Figure 4 As shown, the effective area is 0.1cm 2. Test conditions: spectral distribution AM1.5G, light intensity 100mW / cm 2 , AAA solar simulator (Beijing Zhuoli Hanguang Company), and the JV curve was measured using a Keithly 2400 digital source meter.

[0125] Test results see Fig. 9 The best photoelectric conversion efficiency parameters were: open circuit voltage 1.17V, short circuit current density 24.6mA / cm2, fill factor 84.6%, conversion efficiency 24.3%. After the device was stored in the atmosphere for 3000 hours, it still maintained more than 95% of the initial efficiency.

[0126] Example 3

[0127] The synthetic compound MeO-PhpPACz is synthesized by the following synthesis route:

[0128]

[0129] 1. Synthesis of MeOCz-PhBr

[0130] The raw material 3,6-dimethylcarbazole used to synthesize MeCz-PhBr in Example 1 was replaced with an equal amount of 3,6-dimethoxycarbazole, and MeOCz-PhBr (3.55 g, 92.9%) was obtained according to the synthesis method of MeCz-PhBr. The H NMR spectrum of MeOCz-PhBr is shown in Fig.10 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 7.75-7.65(m,2H),7.55(d,J=2.5Hz,2H),7.45-7.38(m,2H),7.30(d,J=8.9Hz,2H),7.04(dd,J=8.9,2.5Hz,2H),3.95(s,6H).

[0131] 2. Synthesis of MeOCz-PhP

[0132] The raw material MeCz-PhBr used to synthesize MeCz-PhP in Example 1 was replaced with an equal amount of Cz-PhBr, and Cz-PhP (1.04 g, 79.1%) was obtained according to the synthesis method of MeCz-PhP. The H NMR spectrum of Cz-PhP is shown in Fig.11 As shown, the H NMR spectrum data is: 1H NMR(400MHz, CDCl3)δ / ppm 8.02(dd,J=12.9,8.3Hz,2H),7.68(dd,J=8.3,3.5Hz,2H),7.54(d,J=2.4Hz,2H),7.40(d,J=8 .9Hz,2H),7.04(dd,J=8.9,2.5Hz,2H),4.34-4.05(m,4H),3.95(s,6H),1.39(t,J=7.1Hz,6H).

[0133] 3. Synthesis of MeO-PhpPACz

[0134] The raw material MeCz-PhP used to synthesize Me-PhpPACz in Example 1 was replaced with an equal amount of MeOCz-PhP, and MeO-PhpPACz (0.310 g, 80.9%) was obtained according to the synthesis method of Me-PhpPACz. The H NMR spectrum of MeO-PhpPACz is shown in Fig.12 As shown, the H NMR spectrum data is: 1 H NMR(400MHz,DMSO-d6)δ / ppm 7.93(dd,J=12.5,8.1Hz,2H), 7.83(d,J=2.1Hz,2H), 7.70(dd,J=8.2,2.4Hz,2H), 7.38(d,J=8.9Hz,2H), 7.04(dd,J=8.9,2.0Hz,2H), 3.88(s,6H).

[0135] 4. Solar cell devices

[0136] The solar cell involved in this embodiment involves a perovskite solar cell and an organic solar cell, and specifically takes an inverted planar heterojunction perovskite solar cell as an example. Figure 4 1 is a schematic diagram of the structure of the inverted planar heterojunction perovskite solar cell involved in this embodiment, which includes, from bottom to top: (1) a transparent conductive substrate ITO; (2) a monomolecular self-assembled layer (SAM) or a hole transport layer of MeO-PhpPACz; (3) a perovskite light absorbing layer; (4) an electron transport layer (C60); and (5) a copper or silver electrode.

[0137] 1) Cleaning the transparent conductive substrate ITO: the same as in Example 1;

[0138] 2) Preparation of single molecule self-assembled layer (SAM)

[0139] A MeO-PhpPACz solution was prepared; the solution was spin-coated on a transparent conductive substrate ITO at a speed of 4000 rpm for 40 seconds; the obtained film was annealed in nitrogen at 100° C. for 10 minutes;

[0140] 3) Preparation of perovskite light absorbing layer: the same as in Example 1;

[0141] 4) Preparation of electron transport layer: the same as in Example 1;

[0142] 5) Preparation of copper or silver electrodes: the same as in Example 1;

[0143] 6) Testing

[0144] The device structure of the planar heterojunction perovskite solar cell prepared by the above method is as follows Figure 4 As shown, the effective area is 0.1cm 2 . Test conditions: spectral distribution AM1.5G, light intensity 100mW / cm 2 , AAA solar simulator (Beijing Zhuoli Hanguang Company), and the JV curve was measured using a Keithly 2400 digital source meter.

[0145] Test results see Fig.13 The best photoelectric conversion efficiency parameters were: open circuit voltage 1.17V, short circuit current density 24.5mA / cm 2 , fill factor 85.7%, conversion efficiency 24.6%. After the device is stored in the atmosphere for 3000 hours, it still maintains more than 95% of the initial efficiency.

[0146] Example 4

[0147] The synthetic compound NapCz-PhpPACz is synthesized by the following synthesis route:

[0148]

[0149] 1. Synthesis of NapCz-PhBr

[0150] The raw material 3,6-dimethylcarbazole used to synthesize MeCz-PhBr in Example 1 was replaced with an equal amount of 7H-dibenzocarbazole, and NapCz-PhBr (3.28 g, 77.7%) was obtained according to the synthesis method of MeCz-PhBr. The H NMR spectrum of NapCz-PhBr is shown in Fig.14 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 9.27(d,J=8.5Hz,2H),8.09-8.01(m,2H),7.84(d,J=8.9Hz,2H),7.81-7.75(m,2H ),7.75-7.70(m,2H),7.59-7.54(m,2H),7.52(d,J=8.8Hz,2H),7.47-7.40(m,2H).

[0151] 2. Synthesis of NapCz-PhP

[0152] The raw material MeCz-PhBr used to synthesize MeCz-PhP in Example 1 was replaced with an equal amount of NapCz-PhBr, and NapCz-PhP (1.25 g, 86.8%) was obtained according to the synthesis method of MeCz-PhP. The nuclear magnetic resonance hydrogen spectrum of NapCz-PhP is shown in Fig.15 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 9.24(d,J=8.5Hz,2H),8.17-8.08(m,2H),8.08-8.01(m,2H),7.86(d,J=8.9Hz,2H ),7.77-7.66(m,4H),7.66-7.49(m,4H),4.39-4.14(m,4H),1.44(t,J=7.1Hz,6H).

[0153] 3. Synthesis of Nap-PhpPACz

[0154] The raw material MeCz-PhP used to synthesize Me-PhpPACz in Example 1 was replaced with an equal amount of NapCz-PhP, and Nap-PhpPACz (0.405 g, 95.6%) was obtained according to the synthesis method of Me-PhpPACz. The nuclear magnetic resonance hydrogen spectrum of Nap-PhpPACz is shown in Fig.16 As shown, the H NMR spectrum data is: 1 H NMR(400MHz,DMSO-d6)δ / ppm 9.11(d,J=8.5Hz,2H),8.12(d,J=7.8Hz,2H),8.05(dd,J=12.6,8.2Hz,2H),7.95(d,J=9.0Hz,2H),7.81-7.72(m,4H),7.58(dd,J=8.0,6.0Hz,4H).

[0155] 4. Solar cell devices

[0156] The solar cell involved in this embodiment involves a perovskite solar cell and an organic solar cell, and specifically takes an inverted planar heterojunction perovskite solar cell as an example. Figure 4 1 is a schematic diagram of the structure of the inverted planar heterojunction perovskite solar cell involved in this embodiment, which includes, from bottom to top: (1) a transparent conductive substrate ITO; (2) a monomolecular self-assembled layer (SAM) or a hole transport layer of Nap-PhpPACz; (3) a perovskite light absorbing layer; (4) an electron transport layer (C60); and (5) a copper or silver electrode.

[0157] 1) Cleaning the transparent conductive substrate ITO: the same as in Example 1;

[0158] 2) Preparation of single molecule self-assembled layer (SAM)

[0159] A Nap-PhpPACz solution was prepared; the solution was spin-coated on a transparent conductive substrate ITO at a speed of 4000 rpm for 40 seconds; the obtained film was annealed in nitrogen at 100° C. for 10 minutes;

[0160] 3) Preparation of perovskite light absorbing layer: the same as in Example 1;

[0161] 4) Preparation of electron transport layer: the same as in Example 1;

[0162] 5) Preparation of copper or silver electrodes: the same as in Example 1;

[0163] 6) Testing

[0164] The device structure of the planar heterojunction perovskite solar cell prepared by the above method is as follows Figure 4 As shown, the effective area is 0.1cm 2 . Test conditions: spectral distribution AM1.5G, light intensity 100mW / cm 2 , AAA solar simulator (Beijing Zhuoli Hanguang Company), and the JV curve was measured using a Keithly 2400 digital source meter.

[0165] Test results see Fig.17 The best photoelectric conversion efficiency parameters were: open circuit voltage 1.17V, short circuit current density 24.5mA / cm 2 , fill factor 85.9%, conversion efficiency 24.6%. After the device is stored in the atmosphere for 3000 hours, it still maintains more than 95% of the initial efficiency.

[0166] Example 5

[0167] The synthetic compound MMT-PhpPACz is synthesized by the following synthesis route:

[0168]

[0169] 1. Synthesis of MMT-PhBr

[0170] The raw material 3,6-dimethylcarbazole used to synthesize MeCz-PhBr in Example 1 was replaced with an equal amount of 3-methyl-6-methylthiocarbazole, and MMTCz-PhBr (3.63 g, 94.9%) was obtained according to the synthesis method of MeCz-PhBr. The H NMR spectrum of MMTCz-PhBr is shown in Fig.18 As shown, the H NMR spectrum data is: 1H NMR(400MHz, CDCl3)δ / ppm 8.07(dd,J=1.8,0.6Hz,1H),7.89(dt,J=1.6,0.8Hz,1H),7.73-7.64(m,2H),7.39(dd,J=8 .6,1.9Hz,3H),7.27(dd,J=8.5,0.6Hz,1H),7.24-7.18(m,2H),2.57(s,3H),2.53(s,3H).

[0171] 2. Synthesis of MMTCz-PhP

[0172] The raw material MeCz-PhBr used to synthesize MeCz-PhP in Example 1 was replaced with an equal amount of MMTCz-PhBr, and MMTCz-PhP (1.133 g, 86.0%) was obtained according to the synthesis method of MeCz-PhP. The nuclear magnetic resonance hydrogen spectrum of MMTCz-PhP is shown in Fig.19 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 8.10-7.99(m,3H),7.89(dt,J=1.7,0.8Hz,1H),7.69-7.63(m,2H),7.42-7.32(m,3H),7.23 (dd,J=8.5,1.7Hz,1H),4.32-4.13(m,4H),2.57(s,3H),2.53(s,3H),1.40(t,J=7.0Hz,6H).

[0173] 3. Synthesis of MMT-PhpPACz

[0174] The raw material MeCz-PhP used to synthesize Me-PhpPACz in Example 1 was replaced with an equal amount of MMTCz-PhP, and MMT-PhpPACz (0.364 g, 95.0%) was obtained according to the synthesis method of Me-PhpPACz. The H NMR spectrum of MMT-PhpPACz is shown in Fig. 20 As shown, the H NMR spectrum data is: 1 H NMR(400MHz,DMSO-d6)δ / ppm 8.19(dd,J=1.8,0.8Hz,1H),8.08(dt,J=1.6,0.7Hz,1H),8.00-7.90(m,2H),7.70(dd ,J=8.4,2.9Hz,2H),7.41-7.32(m,3H),7.28-7.22(m,1H),2.56(s,3H),2.48(s,3H).

[0175] 4. Solar cell devices

[0176] The solar cell involved in this embodiment involves a perovskite solar cell and an organic solar cell, and specifically takes an inverted planar heterojunction perovskite solar cell as an example. Figure 4 The present invention is a schematic structural diagram of an inverted planar heterojunction perovskite solar cell, which includes, from bottom to top: (1) a transparent conductive substrate ITO; (2) a monomolecular self-assembled layer (SAM) of MMT-PhpPACz or a hole transport layer; (3) a perovskite light absorbing layer; (4) an electron transport layer (C60); and (5) a copper or silver electrode.

[0177] 1) Cleaning the transparent conductive substrate ITO: the same as in Example 1;

[0178] 2) Preparation of single molecule self-assembled layer (SAM)

[0179] A solution of MMT-PhpPACz was prepared; the solution was spin-coated on a transparent conductive substrate ITO at a rotation speed of 4000 rpm for 40 seconds; the obtained film was annealed in nitrogen at 100° C. for 10 minutes;

[0180] 3) Preparation of perovskite light absorbing layer: the same as in Example 1;

[0181] 4) Preparation of electron transport layer: the same as in Example 1;

[0182] In 1×10 -6 Pa vacuum, C60 was deposited on the perovskite surface.

[0183] 5) Preparation of copper or silver electrodes: the same as in Example 1;

[0184] 6) Testing

[0185] The device structure of the planar heterojunction perovskite solar cell prepared by the above method is as follows Figure 4 As shown, the effective area is 0.1cm 2 . Test conditions: spectral distribution AM1.5G, light intensity 100mW / cm 2 , AAA solar simulator (Beijing Zhuoli Hanguang Company), and the JV curve was measured using a Keithly 2400 digital source meter.

[0186] Test results see Fig.21 The best photoelectric conversion efficiency parameters were: open circuit voltage 1.16V, short circuit current density 24.3mA / cm 2 , fill factor 84.8%, conversion efficiency 23.9%. After the device is stored in the atmosphere for 3000 hours, it still maintains more than 95% of the initial efficiency.

[0187] Example 6

[0188] The synthetic compound MON-PhpPACz is synthesized by the following synthesis route:

[0189]

[0190] 1. Synthesis of MONCz-PhBr

[0191] The raw material 3,6-dimethylcarbazole used to synthesize MeCz-PhBr in Example 1 was replaced with an equal amount of 10-methoxy-7H-benzocarbazole, and MONCz-PhBr (3.73 g, 92.7%) was obtained according to the synthesis method of MeCz-PhBr. The H NMR spectrum of MONCz-PhBr is shown in Fig. 22 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 8.77(dd,J=8.3,1.1Hz,1H),8.10(d,J=2.4Hz,1H),8.05-7.98(m,1H),7.82(d,J=8.9Hz,1H),7.79-7.70(m, 3H),7.54-7.48(m,2H),7.48-7.40(m,2H),7.38(d,J=8.9Hz,1H),7.10(dd,J=8.9,2.4Hz,1H),4.04(s,3H).

[0192] 2. Synthesis of MONCz-PhP

[0193] The raw material MeCz-PhBr used to synthesize MeCz-PhP in Example 1 was replaced with an equal amount of MONCz-PhBr, and MONCz-PhP (1.1 g, 79.8%) was obtained according to the synthesis method of MeCz-PhP. The nuclear magnetic resonance hydrogen spectrum of MONCz-PhP is shown in Fig.23 As shown, the H NMR spectrum data is: 1 H NMR(400MHz, CDCl3)δ / ppm 8.76(dd,J=8.4,1.1Hz,1H),8.17-8.03(m,3H),8.00(dd,J=8.2,1.3Hz,1H),7.82(d,J=8.9Hz,1H),7.79-7.65(m,3H),7.5 8(d,J=8.9Hz,1H),7.55-7.43(m,2H),7.10(dd,J=9.0,2.4Hz,1H),4.35-4.14(m,4H),4.03(s,3H),1.42(t,J=7.1Hz,6H).

[0194] 3. Synthesis of MON-PhpPACz

[0195] The raw material MeCz-PhP used to synthesize Me-PhpPACz in Example 1 was replaced with an equal amount of MONCz-PhP, and MON-PhpPACz (0.394 g, 97.7%) was obtained according to the synthesis method of Me-PhpPACz. The hydrogen nuclear magnetic resonance spectrum of MON-PhpPACz is shown in Fig.24 As shown, the H NMR spectrum data is: 1 H NMR(400MHz,DMSO-d6)δ / ppm 8.86(d,J=8.7Hz,1H),8.17-7.87(m,5H),7.81-7.70(m,3H),7.60(d,J=8.9Hz,1H),7.52(d dd,J=8.1,6.9,1.1Hz,1H),7.45(d,J=8.9Hz,1H),7.12(dd,J=8.9,2.4Hz,1H),3.98(s,3H).

[0196] 4. Solar cell devices

[0197] The solar cell involved in this embodiment involves a perovskite solar cell and an organic solar cell, and specifically takes an inverted planar heterojunction perovskite solar cell as an example. Figure 4 The present invention is a schematic structural diagram of an inverted planar heterojunction perovskite solar cell, which includes, from bottom to top: (1) a transparent conductive substrate ITO; (2) a monomolecular self-assembled layer (SAM) of MON-PhpPACz or a hole transport layer; (3) a perovskite light absorbing layer; (4) an electron transport layer (C60); and (5) a copper or silver electrode.

[0198] 1) Cleaning the transparent conductive substrate ITO: the same as in Example 1;

[0199] 2) Preparation of single molecule self-assembled layer (SAM)

[0200] A solution of MON-PhpPACz was prepared; the solution was spin-coated on a transparent conductive substrate ITO at a speed of 4000 rpm for 40 seconds; the obtained film was annealed in nitrogen at 100° C. for 10 minutes;

[0201] 3) Preparation of perovskite light absorbing layer: the same as in Example 1;

[0202] 4) Preparation of electron transport layer: the same as in Example 1;

[0203] 5) Preparation of copper or silver electrodes: the same as in Example 1;

[0204] 6) Testing

[0205] The device structure of the planar heterojunction perovskite solar cell prepared by the above method is as follows Figure 4As shown, the effective area is 0.1cm 2 . Test conditions: spectral distribution AM1.5G, light intensity 100mW / cm 2 , AAA solar simulator (Beijing Zhuoli Hanguang Company), and the JV curve was measured using a Keithly 2400 digital source meter.

[0206] Test results see Fig.25 The best photoelectric conversion efficiency parameters were: open circuit voltage 1.17V, short circuit current density 24.5mA / cm 2 , fill factor 85.17%, conversion efficiency 24.37%. After the device was stored in the atmosphere for 3000 hours, it still maintained more than 95% of the initial efficiency.

[0207] Comparative Example 1

[0208] Me-4PACz was used as a comparative single molecule self-assembled layer, and the device structure was the same as that in Example 1 ( Fig.26 ); the preparation method of the transparent conductive substrate ITO, the monomolecular self-assembled layer or the hole transport layer, the perovskite light absorbing layer, the electron transport layer and the copper or silver electrode is the same as that in Example 1.

[0209] Test results see Fig. 27 and Fig.28 The best photoelectric conversion efficiency parameters obtained with Me-4PACz as the transport layer are: open circuit voltage 1.18V, short circuit current density 25.2mA / cm 2 , fill factor 81.3%, conversion efficiency 24.1%. After the device was stored in the atmosphere for 3000 hours, the device efficiency was only about 74% of the initial efficiency. In Example 1, the best photoelectric conversion efficiency parameters obtained by Me-PhpPACz were: open circuit voltage 1.19V, short circuit current density 25.4mA / cm 2 , fill factor 87.1%, conversion efficiency 26.2%. After the device was stored in the atmosphere for 3000 hours, it still maintained more than 99% of the initial efficiency.

[0210] In summary, the present invention provides a self-assembled monolayer material based on a conjugated linking group, a preparation method thereof, and a solar cell. The chemical structure of the self-assembled monolayer material based on a conjugated linking group is as follows: Among them, the electron donor is an electron-rich group and its derivatives; L is a conjugated linking group. Introducing a conjugated linking group to replace the non-conjugated alkyl linking group in the self-assembled monolayer material can effectively achieve electron delocalization, enhance the intrinsic stability of the monomolecular self-assembled layer molecules and the hole extraction and transmission capabilities; in addition, due to its rigid structure, the order and density of the molecular arrangement of the monomolecular self-assembled layer are significantly improved. And the self-assembled monolayer material based on the conjugated linking group can form a dense monomolecular self-assembled layer on the surface of the conductive substrate, improve the interface contact, and passivate the interface defects; it can form a dipole on the surface of the conductive substrate, improve the surface work function, and promote hole transmission.

[0211] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A solar cell, characterized in that: The solar cell is an inverted perovskite solar cell, which includes, from bottom to top, a transparent conductive substrate, a monomolecular self-assembled layer or a hole transport layer, a perovskite light absorption layer, an electron transport layer and an electrode, wherein the self-assembled monomolecular layer or the hole transport layer includes a self-assembled monomolecular layer material based on a conjugated linking group, and the self-assembled monomolecular layer material based on a conjugated linking group is selected from one of the following chemical structural formulas: